Review : APPLICATION OF FLIPBOOK TECHNOLOGY IN LEARNING AT SMK/SMA - I Gusti Kadek Surya Adnyana (Universitas Suryakancana, 2026)
In recent years, flipbook technology has emerged as an interactive digital medium in education, enhancing the learning process. Flipbooks provide a print-like reading experience enriched with digital features that promote interactivity and accessibility. This article presents a systematic literature review (SLR) of previous studies concerning the application of flipbook technology in secondary education, particularly in vocational and general high schools. The review examines 20 relevant studies to understand the effectiveness, challenges, and opportunities associated with flipbook implementation in education. Keywords: flipbook, digital learning, vocational school, high school, interactive media, systematic literature review